Transformative Islamic Education Management Model at Darul Hijrah Putri Martapura Islamic Boarding School - Zahrah, Zahrah; Sadriah, Sadriah; Yuliani, Yuliani; Mubaraq, Muhammad Zaki; Hermina, Dina (Pascasarjana IAIN Kudus, 2024)
This study aims to analyze the implementation of the Transformative Islamic Education Management Model at Darul Hijrah Putri Martapura Islamic Boarding School, to answer the background of the problem which states the need for change to face the challenges of the times. This research also explains the supporting and inhibiting factors in its application, as well as the implications that occur. The study was conducted at Darul Hijrah Putri Islamic Boarding School, Batung Cindai Alus, Martapura, Banjar Regency. The researchers identified seven informants, including one dormitory leader, three teachers, one student, one parent, and one community leader. The collected data were then analyzed qualitatively using a phenomenological research approach to understand the meaning from the participants’ perspective. The analysis was interrelated and conducted in stages, including data presentation, reduction, verification, and conclusion drawing. The results of this study show that the transformative Islamic education management model at Darul Hijrah Putri Martapura Boarding School involves changes in the organizational structure by decentralizing decision-making and increasing communication and coordination among units. The model also includes expanding the competence of teachers through training and development so that teachers are more up-to-date and regularly conducted so that the duties of teachers can continue to develop in their professionalism, following the curriculum development by adopting changes in the national curriculum, namely integrating the curriculum so that students can focus on religion as well as general subjects to prepare students to face the era of time, and improving facilities to support the transformation of Islamic boarding schools by providing infrastructure such as computers and the Internet to support more modern learning and developing the leadership potential of students through various extracurricular activities. These changes increase the effectiveness of management and the quality of education provided to students. The implementation of this model is supported by several factors, such as an adaptive curriculum. However, there are also challenges such as the reluctance of some boarding school members to change, limited resources, lack of understanding of transformative management, limited competence, management complexity, and communication that is not well established. The transformative Islamic educational management model has positive implications for each educational stakeholder.